Evaluation of growth performance of bamboo (Gigantochloa sp.) in integration with banana (Musa paradisiaca L.) and misai kucing (Orthosiphon stamineus benth.) - Norhidayah Che Soh (Tesis AKUATROP, 2012)
Agroforestry is one of the agricultural designs which integrate woody perennial and agricultural crop. The choice of species and system in agroforestry practice is very important to ensure its productivity. In Malaysia,various agroforestry designs were introduced but the application still limited due to the socio economic problems and also lack of knowledge. Bamboo is one of the suitable species for agroforestry practices because of its various uses and fast growing botanical species.